Gas chromatography-mass spectrometry-based simultaneous quantitative analytical method for urinary oxysterols and bile acids in rats - Kumar, Bhowmik Salil; Chung, Bong Chul; Lee, Young-Joo; Yi, Hong Jae; Lee, Byung-Hoon; Jung, Byung Hwa (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2011)
A simultaneous quantitative assay method for urinary oxysterols and bile acids using GC-MS was developed to investigate the mechanism of liver toxicity induced by drugs or chemicals. Sample preparations were optimized by exploring various extraction solvents, derivatization reagents, and hydrolysis methods to achieve reliable and maximum sensitivity for these two different compound classes. As a result, satisfactory accuracy, precision, and sensitivity were obtained in the validation. The method was then applied to quantify urinary oxysterols and bile acids produced from liver toxicity induced by atorvastatin (250 mg/kg/day). From the results, increases in bile acid levels and decreases in the concentration ratio between cholic acid and chenodeoxycholic acid, which are the distinguishing phenomena observed in serum or bile for liver toxicity, were also observed in urine. Additionally, the mechanism of liver toxicity was investigated with the urinary concentration ratio of product to precursor in the metabolic pathway from cholesterol to bile acids. The results indicated that enzyme activities related to the production and degradation of bile acids, not oxysterols, were significantly changed from liver toxicity. Thus, it was concluded that urinary levels of oxysterols and bile acids could be useful tools for checking liver toxicity and investigating its mechanism. (c) 2010 Elsevier Inc. All rights reserved.
Keywords: CHOLESTEROL OXIDATION-PRODUCTS; COA REDUCTASE INHIBITOR; DRUG-INDUCED HEPATOTOXICITY; LIVER-DISEASE; BEAGLE DOGS; NUCLEAR RECEPTORS; MEDICAL PROGRESS; PLASMA; ATORVASTATIN; METABOLISM